125 Improving fluid prescriptions for inpatient surgical inpatients with diabetes mellitus. (16th November 2020) - Kesavan, Piriyanga; Light, Alexander; Bloom, Oliver
Abstract : Aims: Surgical inpatients with diabetes mellitus are common. We aimed to assess the diabetes management of diabetic adult surgical inpatients. This includes reviewing appropriate medication adjustment with altered eating statuses; fluids prescribed alongside a variable rate intravenous insulin infusion (VRIII); numbers of hypo- and hyper-glycaemic events in those on diabetic treatment and appropriate hypoglycaemia management options prescribed. Methods: We audited current performance against national guidelines from he Joint British Diabetes Societies Inpatient Care Group. A prospective snapshot audit was conducted on surgical patients with diabetes mellitus on 3 surgical wards. Data, including diabetic status, eating status, prescriptions and hypo- and hyper-glycaemic events, were collated by reviewing patient notes, feeding instructions and prescription charts. The results were presented at the surgical governance meeting, including a short teaching session, following which a prospective re-audit was conducted. Results: 65 patients were included in the first cycle and 34 in the second. The percentage of patients on gliclazide with a bedtime snack prescribed increased significantly from 28.6% to 81.8% (p< 0.005). The percentage of patients with hypoglycaemic and hyperglycaemic events decreased but there was no improvement in the VRIII fluid and PRN hypoglycaemia prescriptions. Conclusions: Robust prescription of diabetic medications and fluids is essential for positive outcomes. The significant increase in bedtime snack prescribing for patients on gliclazide was notable progress. However, there is still more to be improved, with the need for greater awareness of the appropriate VRIII fluid prescription and use of PRN hypoglycaemia management protocol. Continual assessment and improvement of diabetic management is recommended to ensure high quality and cost-effective care.